PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN TELEPON SELULER MEREK SAMSUNG DI BANJARMASIN - Said Muhammad; Marijati Sangen (Universitas Lambung Mangkurat, 2017)
The research objective is: To analyze the effect of brand image with the mobile phone purchasing decisions Samsung brand in Banjarmasin. Kind of explanatory research, the sampling technique using a non-probability sampling with the number of respondents as many as 100 people a brand of mobile phone users samsungdi Banjarmasin. The research instrument used questionnaires and measurements with a variable interval scale characteristics of the respondents is the Samsung brand mobile phone users in Singapore. The firm (X1), Other organizations (X2), Evoked universe (X3), Attributes (X4), Benefits (X5) and Attitudes (X6) as independent variables to be tested simultaneously (Simultaneous) and (Partial) influence on purchase decision , The data obtained were analyzed qualitatively and quantitatively by using analytical tools such as validity, reliability, and multiple regression analysis with the classical assumption using multicolinierity test, test heterokedastisitas, test for normality and linearity test, to test the hypothesis by using test of F and test t with IBM SPSS version 23 program. The study states that the universe Evoked (X3), Benefits (X5) and Attitudes (X6) significant positive effect on purchase decisions (Y). While the firm (X1), Other organizations (X2), Attributes (X4) did not significantly influence the purchase decision (Y)